1993
DOI: 10.1007/bf00004503
|View full text |Cite
|
Sign up to set email alerts
|

Changes in tissue and plasma free amino acid concentrations after feeding in Atlantic cod

Abstract: Atlantic cod, Gadus morhua, were maintained on a diet of sandeel and after a 6-day fast were refed a single meal. Concentrations of free amino acids (AAs) were measured in hepatic portal and cardiac blood as well as in the stomach and white muscle at intervals of 6h up to 24h post-feeding. The appearance of both essential and non-essential AAs in the hepatic portal blood was significantly correlated, up to 12h after feeding, to their abundance in the diet. There was a significant decline in total AA concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
4
4

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 26 publications
(34 reference statements)
7
34
4
4
Order By: Relevance
“…Although there were no data on the individual food consumption rates in these studies, Dabrowski (1982) suggested that individual variation in blood and plasma FAA concentrations were largely due to differences in the amount of food ingested. In contrast, other studies have reported that the FAA concentrations change little following feeding (Walton and Wilson 1986;Lyndon et al 1993); FAA concentrations in the white muscle and stomach were relative- Tryptophan and cysteine were not measured after acid hydrolysis.…”
Section: Introductionmentioning
confidence: 64%
“…Although there were no data on the individual food consumption rates in these studies, Dabrowski (1982) suggested that individual variation in blood and plasma FAA concentrations were largely due to differences in the amount of food ingested. In contrast, other studies have reported that the FAA concentrations change little following feeding (Walton and Wilson 1986;Lyndon et al 1993); FAA concentrations in the white muscle and stomach were relative- Tryptophan and cysteine were not measured after acid hydrolysis.…”
Section: Introductionmentioning
confidence: 64%
“…Endogenously formed found both single and double peaks in uptake profiles for cod (Lyndon et al, 1993), but their data show great divergence for the same free AAs between the two sample sites, suggesting ambiguous results due to serially slaughtering a group of fish to obtain blood samples from the HPV and by cardiac puncture. Espe et al also used serial slaughter with Atlantic salmon (Salmo salar) and reported three uptake profiles using caudal puncture to obtain blood (Espe et al, 1993).…”
Section: Experimental Considerationsmentioning
confidence: 98%
“…In fact, it is estimated that 20-50% of the free AAs entering the blood never get past the liver (Hoerr et al, 1991;Hoerr et al,1993;Biolo et al, 1992;Matthews et al, 1993). Lyndon et al tried to estimate the preand post-hepatic free AA plasma levels by serial slaughter of cod (Gadus morhua) and sampling of blood from HPV and cardiac puncture immediately after death (Lyndon et al, 1993). Ash et al (Ash et al, 1998) sampled blood using a double DA and HPV cannulation technique ) from lightly sedated fish but made only one measurement 3·h postprandially.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was not determined in fingerling rainbow trout either (25). Lyndon et al (15) point out the omission of tryptophan content unexplained in the literature. This omission is probably due to the low levels of tryptophan in tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Free amino acid content in various fish species is also differentiated (7,8,15,20). Free amino acid concentration also depends on growth stage, starving, spawning migration, seasonal variation, water temperature and hardness, the storage and processing conditions of fresh fish as raw material, as well as diet.…”
Section: Praca Oryginalnamentioning
confidence: 99%